Training and Motivation on Employee Performance Through Job Satisfaction at PT.Taspen (Persero) KCU Makassar - Yunita, Andi (Scientia Integritas Utama, 2022)
This study aims to analyze the effect of training and work motivation on employee performance through job satisfaction at PT Taspen (Persero) KCU Makassar. This study uses a quantitative approach. The population in this study were all employees working at PT. Taspen KCU Makassar, totaling 42 people. The data collection technique used is through a questionnaire. The data analysis technique used is path analysis. The results of this study indicate that: (1) job training has a direct and significant effect on job satisfaction. (2) motivation has a direct and significant effect on job satisfaction. (3) training has a direct and significant effect on performance. (4) motivation has no significant effect on performance. (5) job satisfaction has a direct and significant effect on performance. (6) training has an indirect effect on performance through job satisfaction. (7) motivation has an indirect effect on performance through job satisfaction.